Factors associated with low coverage of the second dose of Measles containing vaccine among children aged 19–59 Months, Alego-Usonga Sub-County, Kenya, 2020 - Joseph Obiero Ogutu; Gladys Mutethya Francis; Denver Mariga Kamau; Maurice Omondi Owiny; Elvis Omondi Oyugi; Grace Kaverenge Ettyang (Journal of Interventional Epidemiology and Public Health)
Introduction: The coverage of the second dose of the measles-containing vaccine (MCV2) in Kenya has remained low since its introduction in 2013. We assessed the MCV2 vaccination coverage and identified the factors associated with low MCV2 coverage in Alego-Usonga Sub-County, Siaya County, Kenya.